2000
DOI: 10.1021/jp001276w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Vibrational Population of SO(3Σ-) from the Photodissociation of SO2 between 202 and 207 nm

Abstract: Resonance-enhanced multiphoton ionization with time-of-flight product imaging has been used to study the SO 2 + hν f SO( 3 Σ -) + O( 3 P 2 ) channel in the ultraviolet photodissociation of sulfur dioxide at photolysis wavelengths between 202 and 207 nm. These imaging experiments allowed the determination of the vibrational populations of the SO( 3 Σ -) fragment at several wavelengths. A change in the vibrational populations occurs from a distribution where most of the population is in V ) 0 for wavelengths sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 17 publications
6
49
0
Order By: Relevance
“…Similar structure has been observed previously at 193 nm in the TOF experiments of Kawasaki and Sato 16 and Huber and co-workers 15,37 and in the wavelength range of 202-207 nm by Houston and co-workers. 11 To estimate the SO vibrational populations, we fit the speed distributions shown in Figure 4 with a sum of Gaussian functions, each corresponding to the SO cofragment born in a different vibrational state. The widths of the Gaussians, together with the vibrational populations for levels V′ ) 0-5, were used as adjustable parameters in the fit.…”
Section: Spin-orbit State Populationsmentioning
confidence: 99%
“…Similar structure has been observed previously at 193 nm in the TOF experiments of Kawasaki and Sato 16 and Huber and co-workers 15,37 and in the wavelength range of 202-207 nm by Houston and co-workers. 11 To estimate the SO vibrational populations, we fit the speed distributions shown in Figure 4 with a sum of Gaussian functions, each corresponding to the SO cofragment born in a different vibrational state. The widths of the Gaussians, together with the vibrational populations for levels V′ ) 0-5, were used as adjustable parameters in the fit.…”
Section: Spin-orbit State Populationsmentioning
confidence: 99%
“…Braatz & Tiemann (1998) observed a predissociation of SO 2 into SO and O already at the relatively low C 1 B 2 level. Another photodissociation study (Cosofret et al 2000) strongly suggested that this process involves an avoided crossing with a repulsive 1 A 1 state leading to SO þ O if excited vibrational levels of the C 1 B 2 state are reached. Therefore, channel (5a) can possibly proceed following a direct mechanism via a doubly excited state.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant process is thought to be internal conversion arising when mixing occurs between the quasibound continuum of theX ground state with vibronic levels in theC state, but dissociation via a triplet surface could also result from the crossing of theC state by repulsive 2 3 A or 3 1 A states. 24,25,27,30 These conclusions were drawn, in part, from the observation of inverted vibrational distributions in the SO fragment, where >50% of the population is in the v = 2 vibrational level rather than the ground v = 0 state (Table I). 24,26,27,31 The CPUF spectrometer was used to probe the nascent vibrational distribution of SO following photodissociation of SO 2 .…”
Section: B Photochemistry: So 2 + Hν (193 Nm) → O ( 3 P J ) + So (X mentioning
confidence: 97%
“…17,[24][25][26][27][28][29] From those experiments, it was concluded that this reaction occurs via excitation from the ground X 1 A 1 state to theC 1 B 2 state followed by dissociation. However, theC state correlates diabatically to singlet fragments, SO (a 1 ) and O ( 1 D), rather than the observed triplets, SO (X 3 − ) and O ( 3 P), so other pathways must participate.…”
Section: B Photochemistry: So 2 + Hν (193 Nm) → O ( 3 P J ) + So (X mentioning
confidence: 99%